MANAJEMEN STRATEGI DIVISI COLLECTION DALAM UPAYA PENANGANAN PEMBIAYAAN BERMASALAH PADA PT SUZUKI FINANCE INDONESIA CABANG SURABAYA - Rista Juni Andryani; Akmal Suryadi (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2023)
Collection is the management of receivables or accounts receivable as a result of a financing agreement. PT. Suzuki Finance Indonesia is a privately owned business entity engaged in motor vehicle financing. Collection management for PT Suzuki Finance Indonesia Surabaya branch plays an important role for its customers who receive credit facilities. The purpose of writing this journal is to gain knowledge about the application of collection management to credit collection at PT Suzuki Finance Indonesia Surabaya branch. This research uses a qualitative descriptive method, field research methods are carried out by exploring data sourced from locations and library research. The results of this research provide information regarding the importance of collection management to overcome the problem of bad credit. The strategy used by PT Suzuki Finance Indonesia Surabaya Branch in overcoming the problem of bad credit is by monitoring every month, issuing warning letters, withdrawing units and auctioning. The strategy implemented by the collections division to overcome the problem of traffic jams is working effectively.